Effect of triple drug antiretroviral therapy on CD4+ count in pregnant women with HIV and prevention of parent to child transmission - Dwivedi, Akanksha; Gupta, Ratan; Agarwal, Kailash C.; Rani, Kumari U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: India has moved from single drug Antiretroviral Therapy (ART) in 2002 to triple drug ART in 2013 to prevent parent to child transmission of HIV. The aim of the study was to know the effects of triple drug ART on maternal CD4+ count and prevention of HIV transmission to baby along with its adherence, side effects and pregnancy outcome. Methods: A prospective study wsas done in Safdarjung Hospital, New Delhi on 40 HIV positive pregnant women who received single dose combination of triple drug ART. CD4+ count, LFT and KFT were done before beginning of ART and repeated after 6 months of ART. The infants received nevirapine prophylaxis and HIV status was determined by DBS PCR at 6 weeks. Results: The median CD4+ count was 317 and 397 pre and post ART for 6 months respectively (p value<0.001. Low birth weight (LBW) was seen in 43.59% which was statistically significant but confounded as 76.4% of these babies were preterm. 23.08% of babies had an APGAR of < 7 at 1 minute, out of which 77.7% were preterm. Nine out of 39 infants (one had abortion) needed NICU admission. Only one baby (2.56%) was HIV positive who died at 4 months of age due to pneumonia. There was no defaulter and no statistically significant changes in LFT and KFT after 6 months of ART. Conclusions: Triple drug ART offers greater convenience improves fetomaternal outcome and minimize the risk of HIV transmission from mother to child.